Corneal hemangiosarcoma in a dog - Guberman, U. C. [UNESP]; Merlini, N. B. [UNESP]; Perches, C. S. [UNESP]; Fonzar, J. F. [UNESP]; Sereno, M. G. [UNESP]; Mamprim, M. J. [UNESP]; Ranzani, J. J.T. [UNESP]; Brandão, C. V.S. [UNESP] (My University, 2015)
Hemangiosarcoma is a malignant neoplasm and its corneal presentation is uncommon in the dog. The present work reports a case of primary corneal hemangiosarcoma on a mongrel female dog, 20kg, nine years old with a 2 month history of a mass with progressive growth in the right eye. The ophthalmic examination of the right eye showed blepharospasm, moderated conjunctival hyperemia and the presence of a reddish irregular nodule on the dorsal region of the cornea, occupying approximately 60[%] of the cornea. The ocular ultrasound revealed that the neoplasm affected only the cornea and the cytological examination diagnosed a malignant mesenchymal neoplasm. The patient was submitted to keratectomy followed by a third eyelid flap. The excised material was sent for histopathological analysis that diagnosed hemangiosarcoma. Fifteen days after surgery the third eyelid flap was removed and the ophthalmic examination revealed recurrence of the tumor, with the mass occupying the entire cornea and part of the bulbar conjunctiva. The patient was submitted to enucleation. No alterations were observed on the abdominal ultrasound and thoracic radiography, showing the primary characteristics of the disease. Two years after surgery the patient is clinically healthy, without any signs of recurrence or metastasis. Despite the surgical excision of the tumor with free margins, in cases of hemangiosarcoma with aggressive behavior, the enucleation should be considered as a viable option for a successfull therapeutic protocol and better prognosis of the patient.